Crystallization and preliminary crystal structure analysis of the ligand-binding domain of PqsR (MvfR), the Pseudomonas quinolone signal (PQS) responsive quorum-sensing transcription factor of Pseudomonas aeruginosa - Xu, Ningna (International Union of Crystallography, 2012)

(untitled)
The opportunistic bacterial pathogen Pseudomonas aeruginosa employs three transcriptional regulators, LasR, RhlR and PqsR, to control the transcription of a large subset of its genes in a cell-density-dependent process known as quorum sensing. Here, the recombinant production, crystallization and structure solution of the ligand-binding domain of PqsR (MvfR), the LysR-type transcription factor that responds to the Pseudomonas quinolone signal (PQS), a quinolone-based quorum-sensing signal that is unique to P. aeruginosa and possibly a small number of other bacteria, is reported. PqsR regulates the expression of many virulence genes and may therefore be an interesting drug target. The ligand-binding domain (residues 91–319) was produced as a fusion with SUMO, and hexagonal-shaped crystals of purified PqsR_91–319 were obtained using the vapour-diffusion method. Crystallization in the presence of a PQS precursor allowed data collection to 3.25 Å resolution on a synchrotron beamline, and initial phases have been obtained using single-wavelength anomalous diffraction data from seleno-l-methionine-labelled crystals, revealing the space group to be P6(5)22, with unit-cell parameters a = b = 116–120, c = 115–117 Å.